Task-based learning in the classroom for Efl learners: how and why? - Sholeh, Muhammad Badrus (Yayasan Mitra Persada Nusantara, 2023)
In the realm of language teaching and learning, Task-Based Learning (TBL) has emerged as a prominent methodology, garnering substantial attention since the 1980s. This approach, characterized by its focus on real-world tasks as the central unit of instruction, has gained popularity globally, notably in English language classes in Indonesia. TBL's emphasis on establishing a purpose for language use and fostering natural meaning in language learning has contributed to its widespread adoption. This paper delves into the ideas and principles that underpin Task-Based Learning, exploring its effectiveness in classrooms. This study aims to elucidate the rationale for teachers to implement Task-Based Learning in the language classroom and to provide practical insights into the effective implementation of TBL during classroom instruction. The discussion unfolds by introducing and describing the key features of TBL, subsequently delving into its characteristics, approaches, benefits, and framework. To achieve these objectives, a comprehensive literature review will be conducted, drawing on scholarly works, empirical studies, and educational reports related to Task-Based Learning. Additionally, qualitative data will be gathered through interviews with language educators experienced in implementing TBL. The analysis will involve synthesizing findings from the literature review and identifying recurrent themes and successful practices through the teacher interviews. The analysis phase will involve a thematic examination of the literature, exploring the various facets of TBL, including its theoretical underpinnings, practical approaches, and observed benefits in language classrooms. The insights gathered from teacher interviews will be triangulated with the existing literature to provide a nuanced understanding of the challenges and successes associated with the implementation of TBL. This holistic approach aims to offer a comprehensive view of TBL in language education. In conclusion, this paper contributes to the ongoing discourse on language pedagogy by advocating for the implementation of Task-Based Learning in language classrooms. By synthesizing theoretical concepts, practical approaches, and the experiences of educators, the study provides a compelling case for the efficacy of TBL. The insights offered herein aim to empower teachers with the knowledge and strategies needed to successfully integrate TBL into their instructional practices, fostering a dynamic and purposeful language learning environment.